(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the complications, evaluate the initial tumor clearance efficacy, and measure patient satisfaction after treating benign breast tumors using the ultrasound-guided vacuum-assisted breast biopsy (VABB) technique under ultrasound guidance. Patients and methods: A prospective, cross-sectional descriptive study with longitudinal follow-up was conducted on 53 patients with 64 breast tumors previously diagnosed as benign by histopathology. All patients subsequently underwent complete ultrasound-guided VABB for tumor excision and treatment at the Center for Diagnostic Imaging, Military Central Hospital 108, from May 2025 to April 2026. Post-procedural pain scores using the VAS, local complications, tumor clearance rates, and patient satisfaction levels using a 5-point Likert scale were evaluated at the 1-month follow-up. Results: The mean age of the patients was 34.32 ± 11.38 years. The predominant histopathological diagnosis after VABB was fibroadenoma (79.69%). At the 1-month follow-up, the complete tumor clearance rate reached 95.31% per tumor and 94.34% per patient. The mean post-procedural VAS pain score was low (2.77 ± 2.09), with mild pain constituting the majority (64.15%). No severe complications were recorded; the most common complication was localized hematoma occurring in 43.75% of lesions, however, these were predominantly small hematomas (diameter < 3 cm) that were self-limiting and completely resolved after 1 month. The total rate of patients reporting satisfied and very satisfied after the intervention reached 94.34%. Conclusions: Treating benign breast tumors using the ultrasound-guided VABB technique demonstrates high safety, minimal invasiveness, excellent initial tumor clearance, and achieves optimal patient satisfaction.